Changing fire regimes in the Cote d’Ivoire savanna: implications for greenhouse emissions and carbon sequestration - Moussa, K.; Bassett, T.J.; Nkem, J. (Stellenbosch University, 2011)
West African savannas are depicted in the climate change literature as the “burn center” of the planet. This paper suggests that this representation is based on a misunderstanding of burning intensity and the nature of savanna environments. It is argued that burning is not as destructive as perceived and that its effects on vegetation change are more complex than believed. The case study of Katiali examines how farmers and herders use fire as a tool for Sudanian savanna management, and how these practices modify burning regimes and savanna ecosystems over time. The study also investigates the implications of changing burning regimes and vegetation dynamics on greenhouse gas emissions and sequestration of carbon. The theoretical framework of this research builds upon political ecology, which examines the natural resource management practices of ordinary farmers and herders with emphasis on historical-geographical patterns of environmental change, local knowledge, and local specific ecologies. The research was conducted during one dry season from late October 2007 to May 2008 in the Sudanian savanna of northern Côte d’Ivoire. Data were collected through field observations, individual and group interviews, and household surveys. Weather station data were recorded daily. Findings reveal that the Sudanian savanna is a complex environment composed of a mixture of trees, shrubs, grasses, and crops. This diversity is important to recognize in modeling the impact of savanna burning on greenhouse gas emissions. Results also show that farmers and herders increasingly set fires earlier in the dry season to protect orchards and to promote grass regrowth for grazing. Early dry season burning favors the expansion of trees in the Sudanian savannas. The transition demonstrates a shift to a more wooded vegetation cover that could potentially sequester more carbon dioxide than is presently attributed to the system.